(untitled) - Hardy, David (Oxford, 1991)
Scallop farming is an expanding area of business activity in many countries of the world. This book deals with the practicalities of the job for both the beginner and the established farmer. The volume takes a close look at the other farmed shellfish and comparisons are made where appropriate and ideas adopted where practicable. The logistics of handling scallops in any great quantity are considered in detail. The book contains the necessary detail and indeed, encourages the farmer to consider scallop farming from all angles. Many useful suggestions for innovation and cost saving are included. It also contains a basic description of scallop biology.
Keywords: Scallop culture,Scallops